Pluralistic Family: Why They Let Their Children Get Married Early? - Titien Yusnita; Djuara P. Lubis; Musa Hubeis; Rilus A. Kinseng (RIRAI Publisher, 2022)
The decision to marry a child is taken by the parents after holding a family consultation. This was also done by the majority of consensual (16%) and pluralistic (77%) families who were respondents in this study. The purpose of this study is to find out the reasons why pluralistic families allow school-age girls to marry. This research method uses a descriptive qualitative method with depth interviews with several informants such as traditional leaders, government leaders, religious leaders, parents who marry off their children at a young age, and the perpetrators of child marriages themselves. The research was taken in Bogor regency. The results of this study revealed that a pluralistic family in Bogor Regency has the following characteristics: being open with other family members, parents do not want to impose their will on their children, the decision to marry at school age is a mutual agreement, parents choose to marry off their daughters for reasons of concern. socializing, violating religious rules and norms, and also parents want their daughters to stay in the same house or close together. This has become a hereditary tradition. Child marriage also aims to improve the family's economy. Families of child marriages have carried out the tradition of young marriage for three generations following in the footsteps of their grandmothers and mothers who also married young.